Technology-Enhanced Joyful Learning in English as a Foreign Language Reading Comprehension: A Rasch Model Survey - Lusi Elisa; Ag. Bambang Setiyadi; Sumarti Sumarti; Budi Kadaryanto; Flora Flora (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine english as a foreign language learners’ perceptions of technology-enhanced joyful learning in reading comprehension, focusing on how digital tools support comprehension, enjoyment, engagement, and learner autonomy in technology-mediated english reading activities. Methodology: This study used a quantitative cross-sectional survey involving 1,510 english as a foreign language learners. Data were collected through the technology-enhanced joyful learning in english as a foreign language reading comprehension: a rasch model survey questionnaire. the instrument contained 15 likert-scale items covering technology-supported english as a foreign language reading comprehension, Joyful Learning through Technology, and learner engagement and autonomy in technology-enhanced reading constructs. data were analyzed using descriptive statistics and rasch model analysis. Main Findings: The results showed that learners generally perceived technology-enhanced joyful learning positively. Edmodo was the most preferred platform, followed by Kahoot, Google Classroom, Quizlet, Duolingo, and Read&Write. Rasch analysis indicated acceptable item fit and item reliability. Technology was most strongly endorsed for supporting learner autonomy, self-paced reading, and main-idea identification, while comprehension accuracy and reading interest were relatively harder to endorse. Novelty/Originality of this study: This study contributes a rasch-validated measurement framework that integrates technology-supported english as a foreign language reading comprehension, joyful learning through technology, and learner engagement/autonomy. It advances existing english as a foreign language reading research by showing that different technologies provide different affordances for comprehension support, joyful engagement, task motivation, and autonomous learning.